Artificial Intelligence, Digital Finance, and the Green Economy: a Pathway to Climate-Resilient Growth - Kia-Rostami, Nahid (Global journal of Business and Integral Security, 2026)
This study develops a conceptual framework to examine the integration of artificial intelligence (AI), digital finance, and policy mechanisms in promoting a digital and green economy. Drawing on interdisciplinary literature from AI, environmental economics, and sustainability studies, the framework identifies pathways through which AI adoption enhances economic resilience, optimizes resource efficiency, and reduces carbon emissions. Digital finance is positioned as a critical mediator, providing capital and enabling scalability of AI-driven sustainability initiatives, while policy and regulatory support act as moderators to ensure ethical, equitable, and effective implementation. The model also incorporates human capital and workforce readiness as essential factors for translating technological potential into measurable outcomes. Risk and ethical considerations, including algorithmic bias, energy consumption, and digital equity, are addressed to ensure inclusive deployment. By mapping interactions among technology, finance, and governance, the study offers practical guidance for policymakers, businesses, and researchers, advancing an integrated approach to achieving sustainable, climate-resilient economic development.